Sosialisasi Perpajakan sebagai Variabel Intervening dalam Meningkatkan Kepatuhan Pajak (Studi Kasus Wajib Pajak Umkm di KPP Pratama Kudus) - Nofaruddin, Firmana; H, Sunarno; Edris, Mochamad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research aims to analyze the influence of e-filing, e-billing, and e-registration on MSME Taxpayer compliance at KPP Pratama Kudus with tax socialization as an intervening variable. Respondents totaled 140 people. The sampling technique in this research uses accidental sampling, namely individual taxpayers who come and have come to KPP Pratama Kudus. Test the instrument using validity tests and reliability tests. The analysis technique used is SEM (Structural Equation Modeling) AMOS. The results of this research show that: 1) E-filing has a positive and significant effect on tax socialization, 2) E-billing has a positive and significant effect on tax socialization, 3) E-registration has a positive and significant effect on tax socialization, 4) E-filing has a positive and significant effect on taxpayer compliance, 5) E-billing has a positive and significant effect on taxpayer compliance, 6) E-registration has a positive and significant effect on taxpayer compliance, 7) Tax socialization has a positive effect and significant to taxpayer compliance